IN POTENTIAL ANXIETY OF DERAJAT FIGHTING ATHLETES BANDA ACEH CITY IN PREPARATION FOR THE 2025 PRA PORA - Darandi, Teta Arum; Acha, Basyarudin; Ambia, Fachrizal (Jurnal Penjaskesrek, 2025)
In martial arts, particularly in tarung derajat, anxiety plays a crucial role in determining athlete performance. This psychological state arises as a natural response to the pressures of physical competition. While a certain level of anxiety can boost enthusiasm and competitive readiness, if not managed properly, it can hinder concentration, ability, and affect mental resilience. Therefore, managing anxiety is a crucial aspect of mental development so that athletes can perform optimally. Some athletes still experience excessive anxiety, especially as competition dates approach, which can lead to problems such as a lack of focus during performance tests, feeling the opponent is too tough, and often feeling less than optimal. Proper anxiety management will maintain emotional stability and increase the chances of success in competition. This research aims to describe the anxiety of tarung derajat athletes in Banda Aceh City ahead of the Pre PORA. This research uses descriptive methods with qualitative analysis techniques. The population includes all 20 tarung Derajat athletes in Banda Aceh City preparing for the Pre PORA. Data collection was conducted using a closed-ended questionnaire. Data processing techniques used a level and percentage categorization formula. The results showed that most athletes experienced moderate levels of anxiety (75%), while 8% experienced high anxiety and 10% were in the low category. These findings indicate that the majority of athletes experienced moderate anxiety, which is psychologically adaptive and can play a positive role in increasing competitive alertness. However, anxiety that exceeds the optimal threshold has the potential to reduce focus and performance during the 2025 Pre PORA. Therefore, managing anxiety through a psychological coaching approach is an important aspect of maintaining stable performance.